Three-dimensional sensitivity mapping of a handheld magnetic probe for sentinel lymph node biopsy - Akihiro Kuwahata (AIP Advances, 2017)
An experimental apparatus for three-dimensional sensitivity mapping of a handheld magnetic probe with a permanent magnet and a Hall sensor was developed. To optimize the shapes and sizes of the magnets, the sensitivity mappings of two types of magnets, column- and cone-type magnets, were evaluated by the experimental apparatus. The longitudinal sensitivities of column and cone types are 8 and 9 mm, respectively, for 5 μL of magnetic nanoparticles. The measured longitudinal sensitivities agree well with the sensitivities calculated by the finite element method. Furthermore, the maximum lateral resolutions of column and cone types are 4.1 and 3.7 mm, respectively. In terms of the directionality, the sensitivities of column and cone types of the angle of 90° with respect to the probe axis fall approximately to 72% and 50% at 6 mm distance from the probe head, indicating that the cone type has high directionality due to its sharp shape. The measurement of sensitivity mapping revealed that the characteristics of the cone-type magnet are superior to that of the column-type magnet for the identification of sentinel lymph nodes.